PROBLEMS OF TRANSLATING COMPUTER TERMS AND THEIR STRATEGIES - Н.Д., Султaнбaевa; Э.А., Монтaнaй (Journal of Oriental Studies, 2019)
The world is growing in technological direction. Our whole life, entertainments, relationships and even personal remembrances are deeply connected with different types of modern technology. Nowa- days, nevertheless where you are in the world, it is very common to have a communication with each other. Our relationship with new technologies and computers has achieved new meaning, concept and addictedness to them is increasing day by day. The reason of it is that the computer has become a signifi- cant part of the human life. In this context, in order to make the connection between the human and the computer easy, using the computer language (computer terms, lexis, metaphors, jargon and etc.) is con- sidered as an important component in the formation of convenient conditions. The computer language here is computer vocabulary, terms, metaphors, an assistant that helps us to get to know the electronic computing technique closer, use, learn and teach other people to work with computers. This research work represents the problems of translating computer terms and indicates different types of translation. For any translator it is very important to know the basic and effective methods, ways and strategies in order to have a good qualitative translation. Translating terms are one of the most important things that have a big influence in language development. In order to increase the quality of translation almost all countries have specific laws and regulations for the issue of translation. Nowadays, there are various strategies and methods of translating to increase and assist to the work of translators. However, the availability of these methods and strategies does not mean that all done translation works are ideal. Good translation needs, first of all, a professional translator who is familiar with different spe- cific fields, strategies to use in the process of translation, strong knowledge of two or more languages and etc. So, here in this research work we tried to illustrate main problems that a translator can have during his/her work and give several effective methods of translating computer terms. Key words: translation, translation problems, translation methods, strategies.